Model Susceptible Infected Treatment Recovered Susceptible dan Aplikasinya pada Data Sifilis di Indonesia - Purnami Widyaningsih; Ika Amelia Cahyaningrum; Sutanto (Limits: Journal of Mathematics and Its Applications, 2026)
Infectious diseases are diseases that move from one individual to another due to bacteria, viruses, fungi, or parasites that spread directly or indirectly. Syphilis is an infectious disease caused by the bacteria Treponema pallidum. In 2018-2022, there was a 70% increase in syphilis cases in Indonesia. The purpose of this study is to formulate the SITRS model in infectious diseases, apply the model to syphilis data in Indonesia, determine the distribution pattern, identify the success of the syphilis elimination target in Indonesia in 2030. The research methods used are literature and applied studies. The SITRS model is a system of first-order nonlinear differential equations. The model was applied to syphilis data in Indonesia based on 2016-2022. Data from 2016 was used for initial values and 2017-2020 for parameter estimation to obtain the SITRS model on the spread of syphilis in Indonesia. Based on 2021-2022 data, the MAPE value obtained was 8.27% so the model is very accurate. Syphilis cases in Indonesia from 2016-2030 experienced an upward trend. In 2030, it is estimated that there will still be 155,735 syphilis sufferers so the syphilis elimination target is not to be achieved. Simulations are carried out by increasing treatment to 90% until 100% and reducing contact with syphilis sufferers to 0,05%, so that the target of syphilis elimination Indonesia in 2030 can be achieved